Preliminary Study on Novel Expedient Synthesis of 5-Azaisocoumarins by Transition Metal-Catalyzed Cycloisomerization - Yoon, Jeong A; Lim, Changjin; Han, Young Taek (Frontiers in Chemistry, 2020)
A preliminary study to develop a novel synthetic method for 3-aryl-5-azaisocoumarins was performed herein. The cycloisomerization of N-pyranonyl propargylamines in the AgOTf-catalyzed system efficiently afforded the desired 3-aryl-5-azaisocoumarins in a highly regioselective manner. This unprecedented method is expected as an expedient alternative synthetic route to 5-azaisocoumarins because the regioselectivity problem is circumvented, and it is easier to introduce substituents on the pyridine ring compared to previously reported intramolecular lactonization approaches.